PERAN KATIK NAGARI DALAM PENGEMBANGAN DAKWAH DI NAGARI SARIK ALAHAN TIGO KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK - Yondri Popiya; Awis Karni; Zainal (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Abstract. This research is motivated by the low level of spirituality in the Sarik Alahan Tigo community as evidenced by the lack of shared values, low religious knowledge and the lack of places of worship in the Sarik Alahan Tigo village, this was triggered by the technological and economic development of community life in the Sarik Alahan Tigo village. This research method is field research and uses a qualitative approach. The informants for this research were Katik Nagari and the Sarik Alahan Tigo community. Data collection techniques are interviews, observation and documentation. The results of the research show that: 1) Forms of Islamic Da'wah in Katik Nagari in the Spiritual Development of the Community in Nagari Sarik Alahan Tigo, namely: First, Babaliek Ba Surau (Mangaji Sumbayar, Barzanji, Dala'il and Baraja Adat). Second, Activating Sunnah Fasting. Third, LDS Santiago (Sarik Alahan Tigo Da'wah Institute), namely Training for Khatibs and Imams. Fourth, Congregational Prayer. 2) Forms of Da'wah Bil-Hal Katik Nagari in the Spiritual Development of the Community in Nagari Sarik Alahan Tigo, namely: First, Community Social Service, this activity is in the form of Hygiene Education and Community Sharing of Basic Food Supplies. Second, Celebrating Islamic Holidays (PHBI) in Sarik Alahan Tigo. Third, Lambia Ari (Farmers Group). Fourth, Reviving the Manyilau (visiting) Tradition.